Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00424-016-1920-8
|View full text |Cite
|
Sign up to set email alerts
|

Barrier function in the peripheral and central nervous system—a review

Abstract: The peripheral (PNS) and central nervous system (CNS) are delicate structures, highly sensitive to homeostatic changes-and crucial for basic vital functions. Thus, a selection of barriers ensures the protection of the nervous system from noxious blood-borne or surrounding stimuli. In this chapter, anatomy and functioning of the blood-nerve (BNB), the blood-brain (BBB), and the blood-spinal cord barriers (BSCB) are presented and the key tight junction (TJ) proteins described: claudin-1, claudin-3, claudin-5, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
181
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(191 citation statements)
references
References 110 publications
4
181
0
2
Order By: Relevance
“…The BBB occurs at the levels of capillaries and post-capillary venules, and results from the selectivity of TJs and AJs that restrict the passage of solutes, low expression of leukocyte adhesion molecules, and an additional layer of barrier support provided by ensheathing pericytes and astrocyte endfeet (Reinhold and Rittner, 2016). In our model VEEV entry into the CNS occurs along axons of olfactory sensory neurons, however modulation of the BBB may occur through mechanisms that are independent of the inoculation route.…”
Section: Discussionmentioning
confidence: 99%
“…The BBB occurs at the levels of capillaries and post-capillary venules, and results from the selectivity of TJs and AJs that restrict the passage of solutes, low expression of leukocyte adhesion molecules, and an additional layer of barrier support provided by ensheathing pericytes and astrocyte endfeet (Reinhold and Rittner, 2016). In our model VEEV entry into the CNS occurs along axons of olfactory sensory neurons, however modulation of the BBB may occur through mechanisms that are independent of the inoculation route.…”
Section: Discussionmentioning
confidence: 99%
“…Besides endoneurial endothelium, perineurium is generally considered to be another critical structure that composes the blood-nerve barrier (Reinhold and Rittner, 2017). Light and electron microscopy studies revealed that there existed apparent and abundant tight junction strands between neighboring perineurial cells (Thomas, 1963; Gamble and Eames, 1964; Reale et al, 1975; Beamish et al, 1991).…”
Section: Physical Barriers In Peripheral Nervesmentioning
confidence: 99%
“…These physical barriers in the peripheral nervous system may be altered and disrupted under various pathological conditions, especially many immune mediated neuropathies such as Guillain–Barré syndrome (GBS), chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), multifocal motor neuropathy (MMN), and polyneuropathy, organomegaly, endocrinopathy, monoclonal protein, and skin changes (POEMS) (Kanda, 2013; Reinhold and Rittner, 2017; Skaper, 2017). Besides peripheral neuropathies, trauma to the peripheral nervous system can also lead to pathophysiological changes of these physical barriers (Mizisin and Weerasuriya, 2011; Reinhold and Rittner, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A homeostatic microenvironment is of utmost importance to the function of the spinal cord in protection against external, blood‐borne influence. The blood–spinal cord barrier (BSCB) is formed by capillary endothelial cells, a basal lamina, pericytes, and astrocyte foot processes . Endothelial cells are characterized by an absence of cell membrane fenestrations.…”
Section: Introductionmentioning
confidence: 99%